Solusi atas Permasalahan Pengawasan dan Penagihan Outstanding Premi Asuransi Syariah di Indonesia - Bambang Dwi Handoko; Achmad Firdaus (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Islamic Insurance has to increase its profit, especially premium as the main income to maximize the profit. It’s also the purpose of the Sharia Unit Bumiputera Muda 1967 General Insurance. Therefore, it needs strategies and efforts and minimizes the obstacles. One of them is the premium receivables that have matured but not collected or called the outstanding premium. This study aims to analyze problems of the premium receivables that have matured but not collected or called the outstanding premium. Therefore, it needs strategies and efforts and minimizes the obstacles. This study uses a qualitative-quantitative method using Analytic Network Process (ANP). The analysis is focused on internal-external problems and short-term-long term solutions from Sharia Unit Bumiputera Muda 1967 General Insurance that are expected to overcome these problems. The results showed that the most priority problem is internal problems, as follows: premium payment and billing system, internal control, and less effective business processing. Meanwhile, the most priority solution is short-term, as follows: communication and confirmation, performance and operational effectiveness, and structural appreciation and punishment. The results are expected to be implemented by insurers and support the regulator to establish specific policies related to this issue.